Nanocomposites prepared by reactive extrusion: effect of the polymer reactive groups - Oliveira, Manuel (2014)
The interest in the development of polymer nanocomposites by reactive extrusion has been growing in the past years. This work aims to investigate the effect of the polymer reactive groups on chemical reaction extension and consequently, on the morphology of the nanocomposites. For that, two polymers, polypropylene grafted with maleic anhydride (PP-g-MA) and ethylene vinyl acetate (EVA), are used as organic phases and aluminum isopropoxide (Al(Pr-i-O)3) as metal. Nanocomposites are prepared in the melt using sol–gel process. The reaction extension is assessed by FT-IR, rheological measurements, and crosslinking density determination. The dispersion of inorganic nanoparticles is analyzed by SEM and TEM, and EDS is used to identify the presence of metal nanoparticles. Even though, both reactions are successfully accomplished in the melt, the reaction with EVA presents lower reaction activation energy (Ea) and the prepared nanocomposite has a more crosslinked structure. Moreover, a finer morphology with well-dispersed nanoparticles containing aluminum .